Perception Change in Rice Pest Management: A Case Study of Farmers' Evaluation of Conflict Information - K. L. Heong; M. M. Escalada (Journal of Applied Communications, 1997)
A simple rule-of-thumb, or heuristic, in pest management which was in conflict with farmers' prevailing perceptions was communicated to farmers to examine whether their cognitive dissonance would challenge them to evaluate it and change their misperceptions.